The Unmaking of Home in Contemporary Art - Lauzon, Claudette (Book collections on Project MUSE., 2016)
In a world where the notion of home is more traumatizing than it is comforting, artists are using this literal and figurative space to reframe human responses to trauma. Building on the scholarship of key art historians and theorists such as Judith Butler and Mieke Bal, Claudette Lauzon embarks upon a transnational analysis of contemporary artists who challenge the assumption that 'home' is a stable site of belonging. Lauzon's boundary-breaking discussion of artists including Krzysztof Wodiczko, Sanitago Sierra, Doris Salcedo, and Yto Barrada posits that contemporary art offers a unique set of responses to questions of home and belonging in an increasingly unwelcoming world. From the legacies of Colombia's 'dirty war' to migrant North African workers crossing the Mediterranean, The Unmaking of Home in Contemporary Art bears witness to the suffering of others whose overriding notion of home reveals the universality of human vulnerability and the limits of empathy.